SISTEM PENDUKUNG KEPUTUSAN PEREKRUTAN EKS KARYAWAN PTPN II OLEH PT.LANGKAT NUSANTARA KEPONG MENGGUNAKAN METODE MOORA - Jaya Andika Tarigan (Jurnal Abdi Ilmu, 2021)
Employees are one of the most important company assets in supporting the production or progress of the company. Thus, having qualified and dedicated and responsible employees is one of the advantages for every company. For this reason, every company in recruiting employees usually carries out recruitment with a fairly strict selection system so that the results obtained are as desired. In making a decision, of course, data is needed that will support the calculation of a method so that later the best alternative can be obtained based on predetermined criteria data. In the decision support system for the recruitment of former PTPN II employees by PT. Langkat Nusantara Kepong the data used are based on criteria, namely work experience, status, performance, written tests, interviews and health. Based on the weight values of each existing criterion and processed using the Moora algorithm, the best ranking analysis results are A6 Riswanto with a calculation result of 0.144265 with the criteria of 10 years of work experience, married marital status, fairly good performance, 68 written tests, tests interview 80 and health test ie healthy.